Physicochemical Properties of Extracellular Polymeric Substances Produced by Three Bacterial Isolates From Biofouled Reverse Osmosis Membranes - Rehman, Zahid Ur; Vrouwenvelder, Johannes S.; Saikaly, Pascal E. (Frontiers in Microbiology, 2021)
This work describes the chemical composition of extracellular polymeric substances (EPS) produced by three bacteria (RO1, RO2, and RO3) isolated from a biofouled reverse osmosis (RO) membrane. We isolated pure cultures of three bacterial strains from a seven-year-old biofouled RO module that was used in a full-scale seawater treatment plant. All the bacterial strains showed similar growth rates, biofilm formation, and produced similar quantities of proteins and polysaccharides. The gel permeation chromatography showed that the EPS produced by all the strains has a high molecular weight; however, the EPS produced by strains RO1 and RO3 showed the highest molecular weight. Fourier Transform Infrared Spectroscopy (FTIR), Proton Nuclear Magnetic Resonance (1H NMR), and Carbon NMR (13C NMR) were used for a detailed characterization of the EPS. These physicochemical analyses allowed us to identify features of EPS that are important for biofilm formation. FTIR analysis indicated the presence of -1,4 glycosidic linkages (920 cm-1) and amide II (1550 cm-1) in the EPS, the presence of which has been correlated with the fouling potential of bacteria. The presence of -glycoside linkages was further confirmed by 13C NMR analysis. The 13C NMR analysis also showed that the EPS produced by these bacteria is chemically similar to foulants obtained from biofouled RO membranes in previous studies. Therefore, our results support the hypothesis that the majority of substances that cause fouling on RO membranes originate from bacteria. Investigation using 1H NMR showed that the EPS contained a high abundance of hydrophobic compounds, and these compounds can lead to flux decline in the membrane processes. Genome sequencing of the isolates showed that they represent novel species of bacteria belonging to the genus Bacillus. Examination of genomes showed that these bacteria carry carbohydrates-active enzymes that play a role in the production of polysaccharides. Further genomic studies allowed us to identify proteins involved in the biosynthesis of EPS and flagella involved in biofilm formation. These analyses provide a glimpse into the physicochemical properties of EPS found on the RO membrane. This knowledge can be useful in the rational design of biofilm control treatments for the RO membrane.